Tanzania Country Climate Risk Profile Series, Kilolo District - Jalang’o Anyango, Dorcas; Begasha, Edgar; Kweka, Tumainiely (International Center for Tropical Agriculture, 2019)
The agricultural sector in Tanzania has been exposed to high climatic risks for the past several decades (Arce & Caballero, 2015). Experts and farmers assert that climatic risks including unpredictable rainfall, prolonged drought, and increased incidences of pests and diseases have resulted in declining agricultural productivity. Concomitantly, the rivers, streams, soils, and forests from which the rural poor build their livelihoods are on the verge of depletion. The situation has been further exacerbated by unstable commodity prices. Future climatic projections show that the climate trends are likely to worsen in the coming years. For instance, mean annual temperatures in Tanzania are predicted to increase by up to 2.7°C by 2060, and by close to 50% by 2090 (Irish Aid, 2018). Similarly, day and night temperatures are also expected to increase. Rainfall will become increasingly erratic both locally and regionally, with both floods and droughts growing in intensity and frequency.